Evidence of Glacial Erratic Rollover Revealed by 10Be and 26Al Concentration Variations. (24th February 2022) - ZHANG, Zhigang; WANG, Jian; XU, Xiaobin; CHANG, Zhiyang; CUI, Haitao; LIANG, Zhong; CHEN, Xia; SHANG, Zhiyuan
Abstract : Abstract: Cosmogenic nuclide exposure dating is one of the most intensively applied dating methods with which to study glacial geomorphology. Glacial erratics have been the major dating objective in many studies. Some research has proposed that glacial erratics may undergo rollover and re‐transportation during the late exposure stage, which can affect the dating results. However, there is no direct evidence to confirm this possibility. In this study, we collected seven samples from a vertical section inside a glacial erratic in the paleo‐Daocheng ice cap in the southeastern Tibetan Plateau, measuring their contents of the cosmogenic nuclides 10 Be and 26 Al. The results show that from the top to the bottom, the concentrations of 10 Be were (1.21 ± 0.05) × 10 6, (1.00 ± 0.02) × 10 6, (0.88 ± 0.03) × 10 6, (0.77 ± 0.02) × 10 6, (0.75 ± 0.03) × 10 6, (0.95 ± 0.03) × 10 6 and (1.46 ± 0.04) × 10 6 atoms/g. The 10 Be concentrations decreased from (1.21 ± 0.05) × 10 6 atoms/g to (0.75 ± 0.03) × 10 6 atoms/g and then increased to (1.46 ± 0.04) × 10 6 atoms/g, which is not consistent with the theoretical prediction of a gradual decrease. This phenomenon indicates that the glacial erratic may have rolled over at least once. The lower surface of the erratic could have been on top at some time in the past. Therefore, its exposure age was greater than the exposure age that was expected, based on its current orientation. This study provides numerical evidence for an erratic rollover event.